2015
DOI: 10.1186/s13098-015-0112-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of progranulin in diabetes and kidney disease

Abstract: Progranulin (PGRN) is a cysteine rich secreted protein, expressed in epithelial cells, immune cells, neurons, and adipocytes. It was first identified for its growth factor-like properties, being involved in early embryogenesis and tissue remodeling, acting as an anti-inflammatory molecule. In the central nervous system, PGRN has neurotrophic and neuroprotective actions. There is also evidence of PGRN effects on cancer, contributing to tumor proliferation, invasion and cell survival. Recently, PGRN was recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 74 publications
(145 reference statements)
0
40
1
3
Order By: Relevance
“…Progranulin is particularly more highly expressed in visceral adipose tissues of morbid-obese, insulin-resistant patients [22,26]. In a research from Brazil, the authors demonstrated that progranulin may be involved in the pathogenesis of obesity and become a target for metabolic disorder prevention or treatment [27]. When taken altogether, this evidence supports that progranulin plays a regulatory role in glucose and energy homeostasis, and it is possible that it may contribute to the progression of metabolic syndrome [28].…”
Section: Discussionmentioning
confidence: 93%
“…Progranulin is particularly more highly expressed in visceral adipose tissues of morbid-obese, insulin-resistant patients [22,26]. In a research from Brazil, the authors demonstrated that progranulin may be involved in the pathogenesis of obesity and become a target for metabolic disorder prevention or treatment [27]. When taken altogether, this evidence supports that progranulin plays a regulatory role in glucose and energy homeostasis, and it is possible that it may contribute to the progression of metabolic syndrome [28].…”
Section: Discussionmentioning
confidence: 93%
“…For instance, it plays a proinflammatory role in obesity, insulin resistance, dyslipidemia, and metabolic syndrome, while it exerts antiinflammatory effects in wound repair, central nervous system arthritis, acute ischemia-reperfusion injury, and psoriasis [30]. However, there is little knowledge about the normal function of PGRN in the inflammatory response of psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, progranulin has an established role in obesity‐associated T2DM pathogenesis. Specifically, this cysteine‐rich protein decreases insulin‐mediated glucose uptake, disrupts insulin signal pathway, increases adipocyte autophagy, and promotes monocyte recruitment in adipose tissue as well as IL‐6 secretion from adipocytes . Elevated progranulin levels are present in obesity‐associated T2DM, nonalcoholic fatty liver disease, nephropathy, and retinopathy .…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 99%
“…Elevated progranulin levels are present in obesity‐associated T2DM, nonalcoholic fatty liver disease, nephropathy, and retinopathy . However, despite the proinflammatory role of progranulin in T2DM, it exhibits anti‐inflammatory function in various other disorders including arthritis, psoriasis, wound repair, and acute ischemia–reperfusion injury . Modulation of the adipokine is not being currently investigated for T2DM therapy in a clinical trial.…”
Section: Adipokines and Therapies That Modulate Their Activitymentioning
confidence: 99%